Pipeline vs. Choice: The Global Gender Gap in STEM Applications - Isaac Ahimbisibwe; Adam Altjmed; Georgy Artemov; Andres Barrios-Fernandez; Aspasia Bizopoulou; Martti Kaila; Jin-Tan Liu; Rigissa Megalokonomou; Jose Montalban; Christopher A. Neilson; Jintao Sun; Sebastian Otero; et al. (Institute of Labor Economics (IZA), 2025)
Women account for only 35% of global STEM graduates, a share that has remained unchanged for a decade. We use administrative microdata from centralized university admissions in ten systems to deliver the first cross-national decomposition of the STEM gender gap into a pipeline gap (academic preparedness) and a choice gap (first-choice field conditional on eligibility). In deferred-acceptance platforms where eligibility is score-based, we isolate preferences from access. The pipeline gap varies widely, from -19 to +31 percentage points across education systems. By contrast, the choice gap is remarkably stable: high-scoring women are 25 percentage points less likely than men to rank STEM first.
Keywords: I23; I24; N30; 330; gender inequality; STEM gender gap; centralized application platforms